PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN SOCIAL MEDIA MARKETING TERHADAP KAPUTUSAN PEMBELIAN PRODUK FACIAL WASH NIVEA (STUDI PADA GEN Z DI KOTA BANDUNG) - Munindar, Anas Faris; Karamang, Ezra (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine how product quality, brand image, and social media marketing efforts shape the purchasing decisions of Generation Z consumers in Bandung who buy Nivea facial wash products. A quantitative approach was applied using both descriptive and verification designs. A total of 100 individuals who had previously purchased the product were selected through quota and purposive sampling. Data were gathered using an online questionnaire. The collected responses were processed using multiple linear regression with assistance from SPSS. The results indicate that product quality has a meaningful positive influence on consumers’ intention to purchase. Brand image also shows a positive and statistically significant effect. In contrast, social media marketing does not appear to contribute notably to consumers’ buying decisions. These findings suggest that consumers are more strongly guided by their personal experience with the product and their perception of the brand’s credibility rather than by promotional activities on social platforms. The study is expected to help companies design more effective marketing strategies by emphasizing product improvement and strengthening brand reputation among their target audience